Pengembangan Media Pembelajaran Interaktif Melalui Pendekatan Contextual Teaching Learning (CTL) Pelajaran Matematika Kelas IV SD - Dzaky Kosandi; Unik Ambar Wati; Evy Nur Rochmah (Mandalika Mathematics and Educations Journal, 2026)
Mathematics is a discipline that studies forms, structure, and interrelated concepts. Visual aids serve as concrete representations that facilitate learning experiences. The rapid advancement of technology has fostered the development of innovative and creative interactive learning media. This study aims to develop interactive learning media through the Contextual Teacing Learning (CTL) approach for teaching whole number multiplication operations in fourth-grade elementary school mathematics. The subject of this study were the students of Class IV B at SD Kanisius Demangan Baru I. This research was motivated by the limited use of interactive learning media in mathematics learning. This study employed the R&D method using the ADDIE model, which consits of the stages of analysis, design, development, implementation, and evaluation. The validity test results score of 93% in the material aspect, categorized as “highly qvalid” and 82% in the media aspect, categorized as “valid”. Furthermore, the practicality test results scores 92% based on teachers respons and 89% based on students respons, both categorized as “highly practical”. Therefore, the interactive learning media develop in this study are considered valid, practical, and suitable for use in the leraning process.